Pelatihan dan Pendampingan Penerapan SAK ETAP untuk Meningkatkan Kompetensi Guru SMK - Murtanto; Octaviani, Dian; Nurhafifah Amalina; Aprilia, Natasya Angela; Rical nur Udin (PT. Cendekia Sapta Indonesia, 2025)
This training and mentoring program was carried out to enhance the competence of vocational high school (SMK) accounting teachers in West Jakarta, particularly in understanding and applying the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). The program was initiated in response to the relatively low certification rate of SMK teachers, with only 60.06% certified in 2022. The methods employed included counseling, theoretical seminars, hands-on workshops, interactive discussions, and on-site mentoring at participating schools. A total of 20 SMK accounting teachers participated in the program, selected in coordination with P4 West Jakarta. Evaluation was conducted using pre-test and post-test instruments to measure theoretical understanding, the ability to prepare financial statements according to SAK ETAP, and the capacity to implement the knowledge in teaching. The results showed significant improvements: theoretical understanding increased from 40% to 85%, the ability to prepare financial statements rose from 35% to 80%, and active participation in workshops increased from 60% to 90%. Furthermore, the application of the materials in schools improved from 30% to 75%. This program proved effective in enhancing teacher competence while strengthening collaboration among teachers, facilitators, and higher education institutions. In the future, the program’s sustainability is expected to continuously support the improvement of accounting education quality in vocational high schools through ongoing evaluations and more flexible adjustments to training materials according to teachers’ needs.